Mental Health and Spirituality: Qur’anic Teaching and Approaches to Mental Health in the Modern Era - Laila Mawaddah Rofiqoh; Indana Zulfa; Nahid Ayad (Jurnal test, 2025)
Mental health has become an increasingly critical issue in modern society, where stress, anxiety, and depression are prevalent concerns. In this context, exploring how Qur’anic teachings contribute to the understanding and treatment of mental health is essential. This study aims to examine the relationship between Qur’anic teachings and mental health approaches while identifying spiritual principles that support psychological well-being. The research employs a qualitative analysis of relevant Qur’anic verses alongside a literature review on the integration of spirituality into mental health practices. The findings indicate that Qur’anic principles, such as dzikr (remembrance of God), salat (prayer), and tawakkal (reliance on God), offer effective strategies for addressing mental health issues by fostering inner peace and enhancing psychological resilience. The study concludes that integrating spiritual values into mental health approaches not only provides emotional support but also helps individuals cultivate meaning and purpose in life. This knowledge has the potential to contribute to improved mental well-being and overall quality of life in today’s complex society.